SUCCESSFUL IMAGE OF THE LITERARY CRITICISM IN THE SECOND DECADE OF THE TWENTIETH CENTURY - Gilk, Erik (Bohemica Olomucensia, 2014)
TICHÝ, Martin et al. (2013). Desátá léta v podobách kritiky. V Opavě: Slezská univerzita.